Leptatherum (Poaceae): A New Genus Record for the Flora of Turkey - TERZİOĞLU, Salih; ÖZKAN, Kezban (Kastamonu University, 2020)
Aim of study: This study aimed to contribute the vascular plant species diversity of Turkey. Area of study: A8 Trabzon: Sürmene-Çamburnu Nature Park, Scots pine forest, along the road, 10 m in NE Anatolia. Materials and methods: Materials of the present study were collected during the field studies in the years 2019. They were processed according to standard herbarium techniques and stored at KATO herbarium in Karadeniz Technical University. Main results: The genus Leptatherum Nees and its species L. boreale (Ohwi) C.-H. Chen, C.-S. Kuoh & Veldk. (Poaceae) are reported as new genus and species for the vascular flora of Turkey. A new Turkish name of the species is also given. Research highlights: This new vascular plant record is underlined that alien species from Japan and adjacent countries has been continued to introduce in NE Anatolia. Thus, chorological studies should be conducted for monitoring and eliminating the side effects of these invasive taxa in this region of Turkey.
Keywords: 15. Life on land